Long-term Outcomes Following Kidney Transplantation From Donors With Acute Kidney Injury. Issue 9 (September 2019) - Heilman, Raymond L.; Smith, Maxwell L.; Smith, Byron H.; Kumar, Anjushree; Srinivasan, Ananth; Huskey, Janna L.; Khamash, Hasan A.; Jadlowiec, Caroline C.; Mathur, Amit K.; Moss, Adyr A.; Reddy, Kunam S.
Abstract : Background: Kidneys from deceased donors with acute kidney injury (AKI) are more likely to be discarded because of concerns for poor outcomes after transplantation. The aim of this study was to determine the long-term outcomes of a large cohort of patients transplanted utilizing kidneys from deceased donors with AKI. Methods: All patients receiving a deceased donor kidney transplant during a recent 10-year period were included. Acute Kidney Injury Network (AKIN) criteria were used to classify the donors. Donor kidneys with >10% cortical necrosis or more than mild chronic changes were discarded. The primary outcome is the combined endpoint of death or graft loss. Results: The cohort included 1313 kidneys from 974 donors, AKIN stage 0 (no AKI) in 319 (24.3%), stage 1 in 370 (28.2%), stage 2 in 177 (13.5), and stage 3 in 447 (34.0%). Estimated 5-year graft survival (95% confidence interval) was 78.5% (72.5-84.5), 77.8% (72.8-82.1), 83.8% (76.8-88.9), and 84.6% (79.5-88.7) for AKIN donor stage 0 to 3, respectively (log-rank P = 0.10). After adjusting for baseline differences, the hazard ratio (95% confidence interval) for the combined endpoint for the AKIN stage 3 group (relative to AKIN 0 group) was 0.70 (0.45-1.10). Delayed graft function occurred in 44.6% and 75.4% of AKIN 2 and 3 groups, as compared to 33.9% and 33.5% in AKIN 0 and 1 ( P < 0.001). Conclusion: We conclude that transplanting selected kidneys from deceased donors with AKI with preimplantation biopsy showing <10% cortical necrosis and no more than mild chronic changes have excellent long-term graft survival.